From Intention to Action: Hierarchical Sensorimotor Transformation in the Posterior Parietal Cortex12 - Cui, He (Society for Neuroscience, 2014)
While there is a large body of evidence in favor of a clustering of representations of body effectors in the posterior parietal cortex, recent advances have revealed a hierarchical organization beyond a flat intentional map composed of functionally distinct subdivisions operating in parallel at same level. In particular, the parietal reach region (PRR) and dorsal area 5 (area 5d) have been found to play distinct roles in visually-guided reach.